The Influence of Shopping Experience and Price Discount on Repurchase Intention Through Shopping Orientation (Study on Consumers “GoFood”) - Rachmad Nurofiq Ramantyo; Titis shinta Dhewi (CV. AFDIFAL MAJU BERKAH, 2022)
Providing a good shopping experience to consumers and implementing attractive price discounts are some of the efforts that are often used by business people to increase their sales volume. This study aims to determine the direct and indirect influence of shopping experience and price discount on repurchase intention through shopping orientation. This research is an explanatory descriptive quantitative study. GoFood consumers among students became the population in this study then carried out purposive sampling techniques so that 223 respondents were obtained. This research analysis of data using partial least squares structural equetion modeling (PLS-SEM) with WarpPls 7.0 software. The results of the study were obtained 1) shopping experience has a positive and significant direct effect on shopping orientation & repurchase intention 2) price discount has a direct positive and significant effect on shopping orientation & repurchase intention 3) shopping orientation has a direct positive and significant effect on repurchase intention 4) shopping experience has a direct positive and significant effect on Repurchase Intention through Shopping Orientation 5) Price Discount has a direct positive and significant effect on Repurchase Intention through Shopping Orientation. Based on the results of the research, the company should continue to improve the appearance design, optimize services, and continue to provide attractive price discounts.